Application of resource-efficient irrigation technologies in desert pastures of Bukhara region (Texas Journal of Agriculture and Biological Sciences, 2022)
Part of the fertilizers applied to the soil during the irrigation process, the toxic chemicals used against weeds and insects are leached into the underground waters, causing their ecological and meliorational condition to deteriorate. The above-mentioned reasons require the effective use of water reserves allocated to irrigated lands, the system of agro-technological measures that do not adversely affect the ecological situation, the scientific justification and implementation of irrigation methods and procedures.